Communication Research in the EFL Context: Challenges and Directions - Zhou, Nan (Mediterranean Journal of Social Sciences, 2013)
The purpose of this study is to explore the challenges of the existing research on learners’communication behaviors in theEnglish-as-a-foreign-language (EFL), mainly Asian context, and identify the fields which need to be further explored. Byreviewing the research investigating factors influencing EFL learners’ willingness to communicate, this paper argues thatthough learners’ use of English in communication has become the common interest in EFL education research and factorsinfluencing their oral participation have been widely documented, there are limitations.This paper suggests that it is necessaryto conceptualize the communication behaviors of EFL learners in English in terms of situational-specific practices, and toidentify the underlying causes of student self-exclusion from oral tasks, by examining the context in which these students arelocated. In light of the review of the literature, this paper also identifies some variables which need to be taken intoconsideration in future research, such as identity negotiation, investment in English learning, international posture andimagined community.It is hoped that this paper will inform the development of L2 communication research.